Influence of product quality and halal labels on consumer interest in Aira Bulukumba Beauty Clinic - Handayani, Lilies; Nurhazanah, Andi Cahyatri (Indonesian Journal Publisher, 2023)
The objective of this study is to investigate the influence of product quality and labeling on consumer interest in Aira Bulukumba Beauty Clinic. The research methodology employed in this study is quantitative research. The research used primary data, which was collected through the use of questionnaires as the data gathering approach. The approach employed for the analysis of the double linear regression test. The demographic under investigation in this research comprises individuals who identify as Muslim, with a particular focus on the community residing in Bulukumba. The sample utilized in this study comprises a whole population of 50 participants. Data analysis approaches were employed utilizing the SPSS software version 2021. The findings of this study indicate a noteworthy correlation between the quality of the product and consumer interest, so confirming the acceptance of hypothesis H1. The halal certification exerts a significant impact on customer preferences and choices. This suggests that the acceptance of H2 is supported. The acceptability of H3 has a major influence on both the color of the product and the presence of a halal label. The findings of the aforementioned study indicate that the attention of consumers in Aira Bulukumba Beauty Clinic is significantly influenced by the quality of products and the presence of a halal label.